PENCEGAHAN PELANGGARAN PEMILU OLEH BADAN PENGAWAS PEMILU (BAWASLU) KOTA SAMARINDA - Dinny Wirawan Pratiwie (Yuriska: Jurnal Ilmiah Hukum, 2024)
Background: Bawaslu Samarinda efforts to prevent general election violations are a series of activities carried out in carrying out the task of preventing election violations which include coordinating with relevant government agencies, providing advice and increasing public participation in election supervision related to preventing election violations. This research examines and analyzes first, the readiness of the Bawaslu in facing the 2024 Simultaneous General Election, second, the form of preventing General Election Violations carried out by the Bawaslu by using Research Method: The research method used is non-doctrinal, data collection is carried out by library research and field research using observation, then it will be analyzed descriptively qualitatively. By basing existing data, the author describes systematically, factually and accurately the facts and relationships between existing phenomena. Findings: The research results show that the Samarinda City Bawaslu has made efforts to prevent violations at stages throughout 2022. In accordance with its task, namely coordinating and increasing community participation in election supervision. Potential violations and disputes in the election process are very likely to occur at each stage, so efforts with various forms of prevention must continue to be carried out, such as socializing legal regulations to all elements of society, as part of increasing participatory supervision as well as minimizing the occurrence of suspected election violations at each stage of the election. for the sake of creating honest and fair elections. Conclusion: Bawaslu readiness to face the 2024 Simultaneous General Election Bawaslu with the establishment of the Samarinda City Integrated Law Enforcement Center which consists of elements of the Samarinda District Prosecutor's Office, Samarinda Police Elements and Bawaslu Elements. Bawaslu prepares standards for work procedures for supervising the stages of election administration as work guidelines for election supervisors at every level.